QRIS Digital Payment Technology Implementation Strategy for Increase Facilities Transaction on MSMEs at Bank DKI, Syariah Branch, Sidoarjo - Alamsyah, Lutvi; Iqbal, Muhammad (Universitas KH. Abdul Chalim Mojokerto, 2025)
The development of digital technology is driving changes in the payment system in Indonesia, one of which is the presence of QRIS as a digital payment standard initiated by Bank Indonesia. QRIS offers the convenience of non-cash transactions for MSMEs. This study aims to determine the strategy for implementing QRIS digital payment technology to improve transaction convenience for MSMEs at Bank DKI KC Syariah Sidoarjo and identify obstacles faced in its use. The research method used is a qualitative approach with data collection techniques through observation. interviews, and documentation with Bank DKI KC Syariah Sidoarjo and MSMEs. The results of the study show that the QRIS implementation strategy at Bank DKI KC Syariah Sidoarjo through socialization, canvassing , bundling programs , rewards , promotions, and routine assistance, has succeeded in increasing the ease of MSME transactions. As of March 2025, 675 QRIS merchants were recorded with a nominal transaction reaching Rp1,355,580,206, indicating significant enthusiasm and growth in QRIS use among MSMEs in Sidoarjo. However, obstacles such as low digital literacy, lack of understanding of the benefits of QRIS, and limited internet access still need to be overcome. To overcome these obstacles, Bank DKI provides solutions in the form of assistance and routine maintenance . Thus, Bank DKI will continue to strive to increase the use of QRIS to make it more practical and efficient for use among MSMEs.